Use Of Synthetic Skin Substitute (Biobrane) For Plantar Foot Burn - F, Johandi; J, Feng; Lumbun, Ruth; J, Chong; K, Tan B; C, Tan K (Lingkar Studi Bedah Plastik Foundation, 2017)
Background : In Singapore, we experience a unique annual surge of burn cases involving sole of foot during the Hindu fire walking festival. Traditionally, superficial partial-thickness burns of the soles were managed expectantly with regular dressings. We conducted a study to evaluate the effectiveness of an alternative approach of using synthetic skin substitute (Biobrane®). Method : A case series of foot burns admitted October 2016 to the Singapore General Hospital Burns Centre. Burn cases with superficial partial-thickness burn of bilateral sole of foot were included in the study. Exclusion criteria included deep dermal burns and burns that required excision and closure with skin grafting. The patient demographics, time to presentation, medical co-morbidities were analyzed. Outcomes such as length of hospital stay, incidence of infection, need for further surgery, return to pre-injury ambulation status and occupation and cost were studied. Result : A total of 6 partial thickness burns of sole of foot in 3 patients with bilateral foot burns which were treated with Biobrane® were included in the study. Patients were able to return pre-injury functional status- return to work and pre-morbid ambulation status. Neither incidence of wound infections nor any needs for repeat surgery were recorded. However, this group required an increased length of stay and incurred high treatment cost. Conclusion: Biobrane® is a viable adjunct in the management of sole of foot burns. The authors believe there is potential for an improved rate of recovery with Biobrane®. However, the higher cost and length of stay are among its drawbacks. In view of the limitations of our study- case series and small sample size, a prospective and double arm assessment will be required to present definite evidence for synthetic skin substitute in these cases